EXPERENTIAL LEARNING GROUP INVESTIGATION AS EFFORT TO DEVELOPT ENVIRONMENTAL LITERACY ABILITY AT 5th GRADE STUDENTS OF MADRASAH IBTIDAIYAH - Istikomayanti, Yuswa; Suwono, Hadi; Irawati, Mimien Henie (University of Muhammadiyah Malang, 2016)
Â The development of learning tools for Environmental Education to develop students environmental literacy skills are indispensable. Methods of research and development using 4-D Thiagarajan (Define, Design, Develop and Disseminate). The result of the development of the device include syllabi, lesson plans, modules, and assessment instruments tested in class IV A Lesson Study by performing well. The trial results actually (validation testing) with pre-experiment (class IV B) can improve the literacy skills of students include aspects of environmental knowledge, attitudes, and skills and habituation. The trial results actually (class IV B) obtained N-Score Gain knowledge and attitude tests of 0.64 (medium), and N-Gain Score of the attitude scale questionnaire 0.67 (moderate). While aspects of the students skills include practical activities seed, move into the growing medium, and the practice of making compost with N-Gain Score of 0.54 (medium) and 0.69 (moderate). Activity habituation maintain plants and credible form of checks compost with N-Gain Score of 0.48 (moderate). The results of research and development is expected to be utilized by the school and can be distributed to other schools.